1057. CpG-adjuvanted Hepatitis B vaccination improves seroprotection rates in Veterans with HIV. (31st December 2020) - Deming, Meagan; Kottilil, Shyam; Wilson, Eleanor
Abstract: Background: Hepatitis B virus (HBV) remains a global health issue, leading to complications including cirrhosis and hepatocellular carcinoma. Individuals co-infected with Human Immunodeficiency Virus (HIV) and HBV have increased liver-related morbidity and mortality compared to those with HBV mono-infection. Vaccination can effectively prevent HBV infection, but certain critical populations including people living with HIV (PLWH) are less likely to achieve seroprotection (antibody to hepatitis B surface antigen (HBsAb) titer ≥ 10 IU/mL) after vaccination; seroprotection rates (SPR) in PLWH range from 34 to 88% in clinical trials, with improved SPR in those with immunologic reconstitution and viral suppression. With improved immunologic status, SPR have dramatically improved in our Veteran Infectious Disease clinic population. However, a subset of patients remain HBV vaccine nonresponders despite re-vaccination attempts, perhaps due to intrinsic immunologic anergy. We hypothesized that Veterans with HIV who were nonresponders to prior HBV vaccines may respond to a more immunogenic vaccine. Heplisav-B is a 2-dose series, with improved SPR in other classically difficult to vaccinate groups (including the elderly and those with diabetes), but has not yet been studied in individuals with HIV. Methods: HBV vaccine nonresponders who had previously been vaccinated and boosted with median 3 and up to 8 doses of alum-adjuvanted HBV vaccines were re-vaccinated with Heplisav-B. HBsAb titers were assessed at days 0, 30, and 60 to follow vaccine responses. Results: Participants had a median age of 65 (range 44 to 83) and were virologically suppressed on antiretroviral therapy. Enrollment and vaccination was interrupted by the COVID-10 pandemic, but 8 of 10 (80%) enrolled participants had seroprotective titers at day 60, with 6 having titers > 1000 IU/mL. Of the 8 additional participants who had available serologies after the first dose, all were seroprotected, and 3 had titers > 1000 IU/mL.16 of 18 (89%) participants achieved seroprotection with Heplisav-B. Conclusion: Heplisav-B is immunogenic in persons with HIV and should be a reasonable option for HBV vaccination of PLWH who are previous nonresponders. Disclosures: Shyam Kottilil, MD PhD, Arbutus Pharmaceuticals (Grant/Research Support)Gilead Sciences (Grant/Research Support)Merck Inc (Grant/Research Support, Advisor or Review Panel member)